A Summary of Current Findings on Quality of Life Domains and a Proposal for Their Inclusion in Clinical Interventions - Jones, Patrick; Drummond, Peter D. (Frontiers in Psychology, 2021)
Whilst the assessment of quality of life and well-being has burgeoned in the past fifty years, there still remains relatively little research into its treatment in psychology, in spite of the launching of such approaches as positive psychology to widen the ambit of interventions to promote well-being. We posit that there are a number of outstanding quality of life areas that could be integrated into standard therapeutic procedures, and that this would this result in an increase in well-being as a therapeutic outcome. To investigate this an exploratory search of the literature was undertaken of associations between improvements in a life domain and increased well-being or quality of life. Ten domains (relationships, work, money, health and leisure, mindfulness, self-esteem, resolution of past life events, mental style and life management skills) were identified. In view of the substantial evidence of the cumulative impact of these domains upon well-being, it is proposed that conducting a unidimensional clinical intervention that focuses only on the presenting issue is not sufficient. Implications and possible therapeutic pathways are discussed and it is recommended that practitioners include such quality of life domains in their assessment, case formulation, and intervention planning.